Parallel Evaluation of Interaction Nets: Case Studies and Experiments - Mackie, Ian; Sato, Shinya (Electronic Communications of the EASST, 2016)
Interaction nets are a particular kind of graph rewriting system that have many properties that make them useful for capturing sharing and parallelism. There have been a number of research efforts towards implementing interaction nets in parallel, and these have focused on the implementation technologies. In this paper we investigate a related question: when is an interaction net system suitable for parallel evaluation? We observe that some nets cannot benefit from parallelism (they are sequential) and some have the potential to be evaluated in a highly parallel way. This first investigation aims to highlight a number of issues, by presenting experimental evidence for a number of case studies. We hope this can be used to help pave the way to a wider use of this technology for parallel evaluation.